Inovasi Publik Servis Menggunakan E-Government di Kantor Kependudukan dan Pencatatan Sipil Kabupaten Banjarnegara - Tisna Regiana, Era; Rosyadi, Slamet; Utami, Prasetyarti (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The purpose of this study is to determine online innovation in Dindukcapil Banjarnegara, the successful elements of online innovation, government, private sector, sustainability community and local wisdom value. It is for the purpose. Revision of writing qualitative methods, data collection, interviews, and documentation. The information providers are the villages, youth, Dundukcapil and the ADMINISTEK services in the private sector, the village employees, the deputy statement area and the Dandukcapil operator, Dindukcapil's manager. The results of this study indicate that the introduction of innovation is progressing steadily. There is a support for support and local autonomy for potential elements, but it is not perfect yet, but the private sector and the potential and values communities are not yet perfect. There are still private parts that do not want to cooperate, but the local value of wisdom is used as the basis of innovation stability.